Adsorption of resazurin by poly(acrylic acid) hydrogels and evaluation of its use in reduction assay for quantification of cell viability. (February 2021) - Varçin, Merve; Şener, Berke Bilgenur; Bayraç, Ceren
Abstract: Resazurin is a nonfluorescent blue dye which is reduced to a fluorescent pink resorufin via enzymatic activity of living cells. Therefore, a resazurin reduction-based assay serves as an effective method for evaluating cell viability. In this study, resazurin was adsorbed on poly(acrylic acid) (PAA) hydrogels and evaluated for its effectiveness in bacterial and mammalian cell viability assay. The effects of PAA hydrogel and resazurin amounts, pH, temperature, light and agitation on adsorption capacity were examined. The experimental data were fitted to the Langmuir isotherm and pseudo-second order kinetic models with Radj 2 of 0.991 and 0.986, respectively, indicating a chemical monolayer adsorption at fixed adsorption sites via physicochemical interaction between resazurin and PAA hydrogel. In the cell viability assay, resazurin adsorbed on hydrogels gave higher percent reduction at lower bacterial cell concentration. For starting inoculums higher than 1.0 × 10 4  CFU/mL Escherichia coli ( E. coli ), the percent reductions of resazurin adsorbed on hydrogels were not significantly different than that of resazurin free in the growth medium, however, the stability of resazurin in the growth medium was higher when adsorbed on hydrogels. The assays utilizing MCF-7 at three concentrations gave higher reduction results with higher dye stability in the growth medium. It was concluded that adsorption of resazurin on PAA hydrogels improved its stability in medium and thus provided better viability assay conditions for both bacteria and mammalian cell. Graphical abstract: Image 1 Highlights: Resazurin was adsorbed on poly(acrylic acid) (PAA) hydrogels with higher adsorption efficiency. The factors such as hydrogel and resazurin amounts, pH, temperature, light and agitation were examined for adsorption capacity. Adsorption of resazurin on PAA hydrogels is fitted to Langmuir adsorption isotherm and pseudo second-order kinetic model. Adsorption process improved the stability of PAA hydrogels in medium and thus provided better viability assay conditions.